2016
DOI: 10.1111/ajo.12531
|View full text |Cite
|
Sign up to set email alerts
|

Women's questions about medicines in pregnancy – An analysis of calls to an Australian national medicines call centre

Abstract: Pregnant women are concerned about the safety of medication use in pregnancy and a significant proportion overestimate risk. Psychotropic medication and fertility are strong drivers to seek information during preconception. Everyday illnesses and self-medication with OTC medication are a common concern throughout pregnancy, even though many medicines are safe to use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
1
20
1
Order By: Relevance
“…28 Lim et al used the non-adherence subscale of the Beliefs and Behaviour Questionnaire to assess nonadherence in 58 women. 22 Median scores in the two study groups were 8 (6-11) and 7.5 (6)(7)(8)(9)(10)(11); scores could theoretically range from 4 to 20 with higher scores indicating non-adherence. However, no cut-off values were provided to indicate when a participant was considered non-adherent to prescribed therapy; thus, prevalence data on ICS non-adherence were unavailable.…”
Section: Adherence To Ics During Pregnancymentioning
confidence: 98%
See 2 more Smart Citations
“…28 Lim et al used the non-adherence subscale of the Beliefs and Behaviour Questionnaire to assess nonadherence in 58 women. 22 Median scores in the two study groups were 8 (6-11) and 7.5 (6)(7)(8)(9)(10)(11); scores could theoretically range from 4 to 20 with higher scores indicating non-adherence. However, no cut-off values were provided to indicate when a participant was considered non-adherent to prescribed therapy; thus, prevalence data on ICS non-adherence were unavailable.…”
Section: Adherence To Ics During Pregnancymentioning
confidence: 98%
“…In an American survey of 501 women of childbearing age with asthma, 39% discontinued or reduced their asthma medication during pregnancy; of this group, one third did not consult with their physician first . Furthermore, an Australian study of 4573 pregnancy‐related calls to a national medicines call centre found that 53% of the pregnant women indicated that inadequate information was their motivation to call . Whilst Pijpers et al did not specifically report on asthma medication, a second Australian study identified a lack of adequate information about asthma medication during qualitative interviews with 23 pregnant women with asthma …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Notes: a Enquiry topics of studies, besides those by Pijper et al 13 are listed according to their frequency in each individual study. In some studies, one call could contain more than one enquiry topic.…”
Section: Figurementioning
confidence: 99%
“…The force of contractions of the uterus, opens the cervix and this opening is usually reported in cms that is determined by internal examination with one or two fingers. Full opening of the cervix is about 10 centimeters (6)(7)(8). Recently, according to research conducted for normal delivery, high attention has been given to those who already have a C-section (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%